KADAR LEMAK ES KRIM TEPUNG DAUN KELOR (Moringa oleifera) BERDASARKAN VARIASI VOLUME SARI KACANG TANAH (Arhacis hypogea) - Stella Faubun; H Sinay (BIOPENDIX, 2016)
Background: Moringa leaves are rich in nutrients and are a source of antioxidants, but are underutilizedby the community as a food because of its 'langu' smell. In an effort to increase the benefits to extendthe shelf life of products and also attract people to consume the leaves of Moringa leaves leaf can beprocessed into flour, then made ice cream with the addition of peanut essence to see the fat content.Method: This study used Completely Randomized Design (RAL). The data were analyzed using OneWay Anova inferential statistics.Result: There is influence of addition of variation of peanut extract (Arachis hypogea) to fat content inice cream Moringa leaves (Moringa oleifera) that is control 4,457%, addition of 50 ml peanut essenceas much as 5,207%, addition of 75 ml peanut sauce 5,956% , and the addition of groundnut peanuts100 ml fat content of 5.993%.Conclusion: There is an effect of addition of peanut pollen (Arachis hypogea) variation on fat contentin ice cream Moringa leaves (Moringa oleifera).